Policiais militares e política: as associações representativas e suas lutas sociais - REIS, João Francisco Garcia (Universidade Federal do Pará, 2014)
This work show an analyses of the formation´s process of the Association of Military Policies from State of Pará, their fight strategies and the relation with the government. The goal is to investigate the speeches that confirm and deny the collective rights to the militaries from state and how the deal with the contradiction around the citizenship idea, basing on the walk to Cabo´s and Soldiers of Military Policies from State of Pará´s Club (CCSPMPA). The effort rescue the relation established between the military officer and the soldier, their life in barrack (domination, hierarchy, discipline…) and their perspectives about the individual rights, respect and disrespect to laws, participation on claiming movements and the evolution and search for the right to have rights, the results were found though the field research and the oral history; the time cut reaches the period f 1976-2012. The results show that Militaries Officers have characteristics of totals, closed, petrified institutions with scale and vertically structure , that work thought some determinations to the most graduated to the less graduated, where the military officers are explored, dominated by the hierarchy and strength discipline and live without opportunity to have an collective organization, which makes of them not complete citizens; about the motives of demand, we can see the expression that talks about disagreement between the citizenship and the militarism and that despite the domination the military officers wants to participate, to direct their own ways though the collective conception. The absence of collective rights deviate this category of public servicers from the right to have rights.